WHEN POISONED BY TOXIC CHEMICALS MEASURES TO BE TAKEN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
All activities related to land cultivation are carried out in the open air; in times of sharp continental changes in weather conditions, the impact of certain meteorological conditions on people engaged in agricultural work is of great importance, affecting thermoregulation, the general condition of workers, their efficiency, and the level of disease.